Epidemiological study of cervical spine injury in a tertiary care center in South India - Asher, Prasanth; Joseph, Jijo Joseph; Pendro, Varun Singh; Peethambaran, Anilkumar; Prabhakar, Rajmohan Bhanu (International Surgery Journal, 2020)
Background: Cervical spine injuries, according to severity can leave victims with long standing neck pain or varying degrees of weaknesses. The purpose of this study is to determine the epidemiological pattern of cervical spine injury in our hospital so that comparison may be made with other institutions and guidance regarding management may be formulated for the betterment of patients. Methods: This cross-sectional longitudinal study was conducted in Government Medical College, Thiruvananthapuram and included all patients admitted with clinical or radiological evidence of cervical spine injury, over a period of three months. Semi-structured questionnaire was used to collect socio demographic data and details regarding mechanism of injury. Data was analyzed using SPSS. Results: Out of 452 patients enrolled, 69.7% were males and 30.3% were females. Patients were the most commonly between 30-60 years of age (52.4%). Majority (56.1%) had hospital stays lasting less than 10 days. Most common mechanism of injury was road traffic accidents (46.6%). Neck pain was the most common symptom and cervical spine straightening was the most common radiological abnormality. The severity of injuries was more severe in patients who were not restrained by seat belt or using a helmet. Conclusion: Road traffic accidents are the most common cause for cervical spine injuries and majority of patients required only symptomatic care.